2006
DOI: 10.1002/gps.1655
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of attention bias for negative information in late life depression

Abstract: Previous pilot data are confirmed. The emotional Stroop paradigm may have clinical potential for distinguishing geriatric depression and dementia, although as yet this is far from clear. Detailed development work including comparison with depressed and non depressed Alzheimer's patients, will be necessary to demonstrate diagnostic validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 35 publications
(40 reference statements)
3
21
1
Order By: Relevance
“…Nevertheless, it has consistently been demonstrated that elderly patients with emotional disorders, such as geriatric depression or geriatric anxiety disorder, show marked executive control dysfunctions together with fronto-limbic abnormalities [24], [72][74]. Moreover, these patients are typically more strongly distracted by negative stimuli, which is paralleled by decreased prefrontal attention control activity [75], [76]. Taking these findings into account, we propose that the ability to selectively recruit cognitive control processes to assist emotional well-being might be an important resilience factor for emotional health in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has consistently been demonstrated that elderly patients with emotional disorders, such as geriatric depression or geriatric anxiety disorder, show marked executive control dysfunctions together with fronto-limbic abnormalities [24], [72][74]. Moreover, these patients are typically more strongly distracted by negative stimuli, which is paralleled by decreased prefrontal attention control activity [75], [76]. Taking these findings into account, we propose that the ability to selectively recruit cognitive control processes to assist emotional well-being might be an important resilience factor for emotional health in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, depression was associated with a bias toward negative congruent information, mostly due to a difficulty in disengaging from information with a negative valence (for reviews see Gotlib et al, 2004; Mathews and MacLeod, 2005; Clark et al, 2009; Gotlib and Joormann, 2010; Disner et al, 2011; Roiser et al, 2012). Relatedly, in the emotional Stroop task, in which participants’ response time to name the color of an emotional written word indicates their ability to disengage from the emotional context, depressed patients were slower to name the color of negative emotional words, compared to non-depressed controls (Gotlib and McCann, 1984; Broomfield et al, 2007). …”
Section: Perception Of Facial Expression and Its Role In Vulnerabilitmentioning
confidence: 99%
“…As expected, negative emotion conditions revealed greater interference or reduced cognitive control compared with neutral emotion conditions in clinically anxious older adults. On the emotional Stroop task, older individuals with MDD with anxiety (vs. non-depressed and non-anxious controls; Broomfield et al, 2007) or high worry (vs. moderate or low worry; Price et al, 2012) demonstrated slower response times for negative words compared with neutral words. Overall, older individuals with clinical levels of anxiety, as determined by a Diagnostic and Statistical Manual of Mental Disorders (4th ed., text revision, American Psychiatric Association, 2000) diagnosis of GAD or MDD with anxiety, or based on elevated self-reported worry symptoms, may be predisposed to experience greater distraction to negative vs. neutral emotional stimuli.…”
Section: Late-life Anxiety and Cognitive Controlmentioning
confidence: 99%
“…Converging evidence from multiple studies supports these theories by associating impaired cognitive control ability with self-reported anxiety (Beaudreau & O’Hara, 2009) and anxiety status in older individuals (Broomfield, Davies, MacMahon, Ali, & Cross, 2007; Mantella et al, 2007; see Price & Mohlman, 2007 for an alternative view). The term ‘cognitive control’ refers to processes associated with goal-directed behavior in a mechanistic definition of ‘executive functions’ (Miller & Cohen, 2001).…”
Section: Introductionmentioning
confidence: 99%